PENGARUH DANA TRANSFER KE DAERAH DAN DANA DESA TERHADAP TINGKAT KEMISKINAN DESA DENGAN PENDAPATAN ASLI DAERAH SEBAGAI VARIABEL MODERASI - Setyawan, Dendy (Jurnal Ilmu Ekonomi, 2023)
Poverty is a social problem that has always been an important issue in regional development programs because it is related to people's welfare. This research was conducted to determine the magnitude of the influence of Regions' Transfer Funds and Village Funds directly on the Poverty Level as well as by moderating Local Own-source Revenue in East Java during the period 2015–2021. The data analysis method used is the SEM-PLS analysis model. The results showed that the Village Fund variable had a positive effect on the Poverty Level, but Regions' Transfer Funds had no effect while Local Own-source Revenue did not moderate the effect of Regions' Transfer Funds and Village Funds on Poverty Levels.